Radical Women: Latin American Art, 1960-1985. - Fajardo-Hill; Alonso, Rodrigo; Giunta, Andrea (Hammer Museum and Delmonico Books, Prestel : Los Angeles, 2017)
Bemberg, Maria Luisa ; Cancela, Delia; Carnevale, Graciela ; d'Amico, Alicia & Facia, Sara ; Dowek, Diana; Gutierrez Marx, Graciela; Hirsch, Narcisa; Kamien, Ana & Marini, Marilu; Lublin, Lea; Maresca Liliana; Minujin, Marta; Orensanz, Marie; Pksa, Margarita; Porter, Liliana; Puzzovio, Dalila; Schvartz, Marcia; Alavres, Maria; Andjar, Claudia; Araujo, Martha; Chaves Barcellos, Clark, Lygia; Cordeiro, Analivia; Dardot, Liliane; de Barros, Lenora; de Freitas, lole; Geiger, Anna Maria; Gross, Carmela; Maiolino, Anna Maria; X, Marcia; Mussi, Ana Vitoria; Pape, Lygia; Parente Leticia; Pimentel, Wanda; Sa, Neida; Silveira, Regina; Soares, Teresinha; Toledo, Amelia; Tostes, Celeida; Vater, Regina; Barrios, Gracia; Brintrup, Sybil & Meneses, Magali; Bru, Roser; Camiruaga, Gloria; Donoso, Luz; Eltit, Diamela; Errazuriz, Paz; Errazuriz, Virginia; Parra, Catalina; Rosenfeld, Lotty; Toro, Janet; Vargas Pereira, Eugenia; Vicuna, Cecilia; Barney, Alicia; Bernal, Delfina; Bursztyn, Feliza; Cano, Maria Teresa; Gonzalez, Sonia; Gutierrez, Sonia; Lamassonne, Karen; Llano-Mejia; Lucena, Clemencia; Marmolejo, Maria evelia; Modiano, sara; Navarro, Rosa; Restrepo, Patricia; Zarate, Nirma; Cabezas, Victoria; Eiriz, Antonia; Mendieta, Ana; Perze, Marta Maria; Sanchez, Zilia; Azurdia, Margarita; Andrade, Yolanda; Bustamante, Maris; Cuevas, Ximena; Grobet, Lourdes; Gruner, Silvia; Horna, Kati; Iturbide, Graciela; Jimenze, Ana Victoria; Lara, Magali; Mayer, Monica; Minter, Sarah; Palau, Marta; de gallina Negra, Polvo; Rippey, Carla; Rodriguez, Jesusa; Weiss, Pola; Eleta, Sandra; Blinder, Olga; Morselli, Margarita; Burga, teresa; Gomez-Sanches, Gloria; Hamann, Johanna; Santa Cruz, Victoria; Marichal, Poli; Medin, Frieda; Alvarez Munoz, Celia; F. Bacca, Judith; Carrasco, Barbara; Carvalho, Josely; Castro, Isabel; Lopez, Yolanda; Martinez-Canas, Maria; Palaciao Whitman, Sylvia; Rivera, Sophie; Salasar Simpson, Sylvia; Valdez, Patssi; Romero, Nelbia; Trujillo, teresa; Gonzalez : etc.
Radical Women: latin American Art, 1960-1985, Hammer Museum, Los Angeles, 15 september 2017- 31 december 2017
boek